Human factors and ergonomics in home care: Current concerns and future considerations for health information technology - Or, Calvin K.L. (2009)
Sicker patients with greater care needs are being discharged to their homes to assume responsibility for their own care with fewer nurses available to aid them. This situation brings with it a host of human factors and ergonomic (HFE) concerns, both for the home care nurse and the home dwelling patient, that can affect quality of care and patient safety. Many of these concerns are related to the critical home care tasks of information access, communication, and patient self-monitoring and self-management. Currently, a variety of health information technologies (HITs) are being promoted as possible solutions to those problems, but those same technologies bring with them a new set of HFE concerns. This paper reviews the HFE considerations for information access, communication, and patients self-monitoring and self-management, discusses how HIT can potentially mitigate current problems, and explains how the design and implementation of HIT itself requires careful HFE attention.